A Constitutively Mannose-Sensitive Agglutinating Salmonella enterica subsp. enterica Serovar Typhimurium Strain, Carrying a Transposon in the Fimbrial Usher Gene stbC, Exhibits Multidrug Resistance and Flagellated Phenotypes - Kuan-Hsun Wu; Ke-Chuan Wang; Lin-Wen Lee; Yi-Ning Huang; Kuang-Sheng Yeh (The Scientific World Journal)
Static broth culture favors Salmonella enterica subsp. enterica serovar Typhimurium to produce type 1 fimbriae, while solid agar inhibits its expression. A transposon inserted in stbC, which would encode an usher for Stb fimbriae of a non-flagellar Salmonella enterica subsp. enterica serovar Typhimurium LB5010 strain, conferred it to agglutinate yeast cells on both cultures. RT-PCR revealed that the expression of the fimbrial subunit gene fimA, and fimZ, a regulatory gene of fimA, were both increased in the stbC mutant when grown on LB agar; fimW, a repressor gene of fimA, exhibited lower expression. Flagella were observed in the stbC mutant and this phenotype was correlated with the motile phenotype. Microarray data and RT-PCR indicated that the expression of three genes, motA, motB, and cheM, was enhanced in the stbC mutant. The stbC mutant was resistant to several antibiotics, consistent with the finding that expression of yhcQ and ramA was enhanced. A complementation test revealed that transforming a recombinant plasmid possessing the stbC restored the mannose-sensitive agglutination phenotype to the stbC mutant much as that in the parental Salmonella enterica subsp. enterica serovar Typhimurium LB5010 strain, indicating the possibility of an interplay of different fimbrial systems in coordinating their expression.